2022
DOI: 10.1186/s12891-022-05782-z
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in factors associated with neck pain among undergraduate healthcare students: a cross-sectional survey

Abstract: Background Neck pain is widespread among students in healthcare-related fields. Although neck pain is more prevalent in females, since most research involves mixed-sex samples we know very little about sex differences in contributors to neck pain. Thus, this study sought to explore sex differences in the risk factors for neck pain in this high-risk population. Methods This cross-sectional study was conducted in China in 2021 and included a sample o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 50 publications
1
7
0
2
Order By: Relevance
“…The findings are in line with other studies which also reported the presence of depression 6,14,[25][26][27] and anxiety 6,25,27 symptoms in patients with NSNP compared to pain-free controls. However, in contrast to previous studies, [26][27][28] no significant difference in catastrophizing and kinesiophobia was found between participants with neck pain and healthy controls.…”
Section: Psychological Factors and Cpmsupporting
confidence: 93%
See 3 more Smart Citations
“…The findings are in line with other studies which also reported the presence of depression 6,14,[25][26][27] and anxiety 6,25,27 symptoms in patients with NSNP compared to pain-free controls. However, in contrast to previous studies, [26][27][28] no significant difference in catastrophizing and kinesiophobia was found between participants with neck pain and healthy controls.…”
Section: Psychological Factors and Cpmsupporting
confidence: 93%
“…3,4 However, a high prevalence of neck pain has been found in University students despite their young age. 5,6 Regardless of high investments in the study and treatment of neck pain, the age-standardized point prevalence, annual incidence, and years lived with disability due to neck pain have not changed over the last 30 years, 2 and more than one-fifth of acute neck pain patients continue from suffering from recurrent episodes or persistent pain. 7 Most patients with neck pain did not show pathoanatomical causes that could explain their pain 8 or associated trauma, being diagnosed with non-specific neck pain (NSNP).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The worldwide COVID-19 pandemic has caused significant disruptions in people's daily lives, with medical students particularly affected. The implementation of lockdown measures has had a major negative impact on students' academic pursuits, daily habits, and mental well-being, creating an environment conducive to the emergence or exacerbation of neck pain [19]. There have been significant changes in the worldwide education system.…”
Section: Covid-19 and Neck Painmentioning
confidence: 99%